The anatomy of rage: conceptualization, operationalization, and validation of a new measurement scale - Michałkiewicz, Natalia; Strojny, Paweł; Strojny, Agnieszka (Frontiers in Psychiatry, 2025)
IntroductionDespite its prevalence among gamers, rage remains an understudied phenomenon in digital gaming. The present study aimed to conceptualize rage as an emotional response to in-game failure or frustration and to develop a reliable and valid self-report instrument to measure this experience.MethodsThe study was conducted in two phases. In the first, theoretical and qualitative phase, a focus group and expert assessment procedure were used to define the construct of rage in gaming and develop initial items. In the second, empirical phase, an international sample of 267 participants (126 females, 124 males, 17 identifying as other; aged 18–52) completed an online survey. Exploratory and confirmatory factor analyses were conducted alongside reliability testing and correlational analyses with related psychological constructs (DERS-SF, IGDS9-SF, BAQ, PHQ-9, GAD-7).ResultsFactor analyses resulted in an 11-item scale with a three-factor structure: Emotion, Cognition, and Arousal. The scale demonstrated good psychometric properties, including satisfactory reliability and model fit. Correlations with related constructs indicated significant associations between rage, gaming disorder symptoms, and emotional dysregulation, suggesting that gaming rage is linked to maladaptive emotional and behavioral patterns and warrants further investigation.ConclusionThe developed scale offers a preliminary tool for future research on rage in video game players. Its application may contribute to a more comprehensive understanding of this phenomenon and its psychological correlates.